Adelphi in the New Millennium: A Socio-Stylistic Analysis of Adelphi’s Best-Selling Books of the Last Two Decades (Altre Modernità, 2025)
In January 2001, an article by Olivia Barbella titled Il successo targato Adelphi appeared in Tirature. In her essay, Barbella observed how authors such as Schine, McCourt, Márai, McGrath, Ferrandino, Fine, and MacDonald, published in the early 2000s, managed to achieve significant public success thanks to the quality guarantee offered by Adelphi’s distinctive editorial approach. The rise of the Milanese publishing house, which began in the second half of the 1980s, was later confirmed by the enduring presence of its titles both in bestseller rankings and in qualitative hierarchies curated by cultural blogs for a broad audience, such as the classifiche di qualità compiled by the online magazine L’Indiscreto. On one hand, the consistent presence among bestsellers indicates the widespread dissemination of Adelphi’s titles; on the other hand, alternative rankings to sales charts underscore the symbolic value attributed to the Adelphi’s brand within the cultural discourse of the 21st century. Twenty-three years after Barbella’s article, a new examination of Adelphi’s bestsellers seems necessary in light of their growing success. This paper aims to analyze in detail, from stylistic, sociological, and publishing perspectives, the Adelphi volumes that have appeared in bestseller lists and qualitative rankings during the first two decades of the 21st century. In the context of Adelphi’s established reputation, the ultimate goal is to identify the recurring elements in the selection of texts, their presentation to readers, and the public’s response.
Keywords: Adelphi; Calasso; publishing; best-seller; quality rankings